Children's perceptions of illness and health: An analysis of drawings. (June 2016) - Mouratidi, Paraskevi-Stavroula; Bonoti, Fotini; Leondari, Angeliki
Objective: The purpose of this study was to explore possible age differences in children's perceptions of illness and health and to what extent these differ from adults' perceptions. Design: Cross-sectional design. Setting: Selected nursery and primary schools in Greece. Method: The sample consisted of 347 children aged 5–11 years and 114 adults – as a comparison group. Each participant was asked to create two drawings, depicting illness and health respectively, and to give an explanatory title for each. Drawings were categorised into three main categories, depending on the aspect of illness or health depicted, namely biomedical, psychosocial and lifestyle. Results: Older children produced more multifaceted depictions of illness and health than their younger counterparts, while the youngest group had difficulty to represent the two concepts clearly. A comparison of children's perception of illness and health revealed that the first is perceived mainly as a biomedical phenomenon, while the latter as a psychosocial one. Finally, a comparison of adults' and children's representations showed that children understand illness mainly through its biomedical dimensions, unlike adults who seem to prefer to stress psychosocial ones. Conclusions: Knowledge of children's subjective perceptions of illness and health may be useful in designing health prevention programmes and for medical professionals working with children experiencing chronic illness.